Implementasi Surat Pernyataan Kesanggupan dan Pemantauan Lingkungan Hidup (SPPL) di Kabupaten Banyumas - Dwi Istiningsih; Eddy Poerwodihardjo (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2017)
In conducting business or activity, there are legislation that must be obeyed. In the context of environmental regulations, there are several types of documents that must be made by business actors / development activities.One of these documents is SPPL or Statement of Environmental Management and Monitoring.During the construction and after the development activities are completed there will be some negative impacts on the environment, both on the biotic environment, abiotic and socio-cultural surrounding communities. Whereas there should be no adverse environmental impact, if the SPPL is really implemented properly.The environment minister has drafted a regulation on guidelines for the preparation of environmental documents containing the plan of action and activities to be undertaken by the initiator during and after the building activities. Here the author limits on the discussion of article 1, paragraph 3, which is about the Statement of Environmental Management and Monitoring Capacity.The potential environmental impacts, management and monitoring of environmental impacts shall be the responsibility of the developer but Implementation of the Statement of Environmental Management and Monitoring Statement has not been fully implemented by the initiating party.Officers have not conducted effective and continuous monitoring of SPPL implementation by the proponent. This results in the initiator often not passing on the matters contained in the SPPL, and is merely a formality only as a condition of the permit of the IMB.There is an "omission" of violations in the implementation of SPPL so that violations become commonplace and do not generate "guilt" by the initiator.It takes clear and decisive sanctions that give rise to "shame" and deterrent effect indiscriminately so that the implementation performance of the SPPL is so maximally that the Environment can be completely protected from damage and pollution.Keywords: capability, monitoring, sanction ABSTRAKDalam melakukan usaha ataupun kegiatan, terdapat peraturan perundang-undangan yang harus dipatuhi. Dalam konteks peraturan lingkungan hidup, terdapat beberapa jenis dokumen yang harus dibuat oleh pelaku usaha/kegiatan pembangunan.Salah satu dari dokumen tersebut adalah SPPL atau Surat Pernyataan Kesanggupan Pengelolaan dan Pemantauan Lingkungan Hidup.Selama pelaksanaan pembangunan dan setelah kegiatan pembangunan selesai maka akan terjadi beberapa dampak negatif terhadap lingkungan, baik terhadap lingkungan biotik, abiotik maupun sosial budaya masyarakat sekitarnya.  Padahal seharusnya tidak terjadi dampak yang merugikan lingkungan, apabila SPPL benar-benar diimplementasikan dengan baik.Menteri lingkungan hidup telah membuat peraturan tentang pedoman penyusunan dokumen  lingkungan hidup yang memuat tentang rencana aksi dan kegiatan yang harus dilakukan oleh pemrakarsa  saat dan setelah melakukan kegiatan membangun. Di sini penulis membatasi pada pembahasan pasal 1 ayat 3, yaitu tentang Surat Pernyataan Kesanggupan Pengelolaan dan Pemantauan Lingkungan.Dampak Lingkungan yang dapat terjadi, pengelolaan dan pemantauan dampak lingkungan menjadi tanggungjawab pemrakasa,Namun Implementasi  Surat Pernyataan Kesanggupan Pengelolaan dan Pemantauan Lingkungan Hidup belum sepenuhnya dilaksanakan dengan baik oleh Pihak Pemrakarsa.Petugas  belum melakukan pemantauan secara efektif dan kontinyu atas pelaksanaan SPPL oleh pemrakarsa. Hal ini menyebabkan pemrakarsa sering tidak melalukan hal-hal yang tercantum di dalam SPPL, dan hanya bersifat formalitas  saja sebagai syarat perijinan IMB.Terjadi  “pembiaran “ terhadap pelanggaran-pelanggaran dalam pelaksanaan SPPL sehingga pelanggaran menjadi suatu yang lumrah dan tidak menimbulkan “rasa bersalah “ oleh pemrakarsa